Penerapan Model Pembelajaran Picture and Picture Pada Materi Interaksi Keruangan dalam Kehidupan di Negara-negara ASEAN untuk Meningkatkan Hasil Belajar IPS Peserta Didik Madrasah Tsanawiyah - Habibah, Fatimatuzzahro; Purnomo, Agus; Ruja, I Nyoman; Kurniawan, Bayu (Edusia: Jurnal Ilmiah Pendidikan Asia, 2023)
This research aims to test the effectiveness of implementing the picture-and-picture learning model in improving student learning outcomes. This research is action research carried out in class VIII H of MTs Negeri 5 Nganjuk, East Java. The research subjects were 32 students in class VIII H of MTs Negeri 5 Nganjuk. This research consists of 2 cycles, namely cycle I and cycle II. Each cycle involves planning, action, observation, and reflection. The research results show that being given a picture-and-picture learning model can improve students' social studies learning outcomes. There was an increase in the average post-test score for cycle I and cycle II. Students who achieved the KKM also experienced an increase. Most students think applying the picture and picture model is fun because it is easier to learn and memorize.